PERKEMBANGAN PERUMAHAN DAN KAWASAN PERMUKIMAN (PKP) PADA KAWASAN SEKITAR JALAN RINGROAD 2 MANADO - Pakpahan, Ruicosta P; Takumansang, Esli D; Sondakh, Julianus A. R. (SPASIAL, 2021)
Housing and Settlement Areas (PKP) are the forerunners of cities that have existed for thousands of years which aim to provide better protection to a large number of residents from various community groups. Housing and residential areas in Indonesia are growing, which are largely influenced by the community itself. The development of housing and settlement areas (PKP) in North Sulawesi, especially in the city of Manado, is growing. Where housing and settlement areas are marked by the increasing number of residents and residential houses that were formerly vacant land become residential land. With the increase in population, it is accompanied by the development of housing and residential areas as well as infrastructure, facilities or utilities. The research objectives are to identify housing conditions and residential areas in the area around Manado RingRoad 2 road and analyze the pattern of housing development and residential areas in the area around Manado Ring Road 2 road. The analytical methods in this study include spatial time series analysis to determine the development of housing and settlement areas and use the nearest neighbor calculation analysis to determine the pattern of housing development and settlement areas. The results of the study showed that there was a development of housing conditions and residential areas increased by 305.54 ha from 2011-2021. The pattern of housing development and residential areas in 2011-2021 experienced a housing pattern from clustered to random.Keywords : Development, Pattern, Housing and Settlement Area